2019
DOI: 10.2967/jnumed.118.214726
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-PET Imaging to Assess Target Engagement: Experience from 89Zr-Anti-HER3 mAb (GSK2849330) in Patients with Solid Tumors

Abstract: PET imaging with radiolabeled drugs provides information on tumor uptake and dose-dependent target interaction to support selection of an optimal dose for future efficacy testing. In this immuno-PET study of the anti–human epidermal growth factor receptor (HER3) mAb GSK2849330, we investigated the biodistribution and tumor uptake of 89 Zr-labeled GSK2849330 and evaluated target engagement as a function of antibody mass dose. Methods: 89 Zr-GSK2849330 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 27 publications
3
57
0
Order By: Relevance
“…Target engagement assessment is an important parameter for optimizing the BED of antibodies and antibody conjugates, and it can be used to construct pharmacokinetic/pharmacodynamic (PK/PD) models bridging animal and human testing. [1][2][3][4][5] Flow cytometry, [5][6][7][8] enzyme-linked immunosorbent assays (ELISAs), 9 and mass spectrometry 10 are commonly employed to measure the target saturation of monoclonal antibody (mAb) binding to the receptors of circulating blood cells, and immunohistochemistry (IHC) is usually used to assess the selective localization of target proteins in tissue specimens. 8,11 Studies have shown that molecular imaging can be used to assess target engagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target engagement assessment is an important parameter for optimizing the BED of antibodies and antibody conjugates, and it can be used to construct pharmacokinetic/pharmacodynamic (PK/PD) models bridging animal and human testing. [1][2][3][4][5] Flow cytometry, [5][6][7][8] enzyme-linked immunosorbent assays (ELISAs), 9 and mass spectrometry 10 are commonly employed to measure the target saturation of monoclonal antibody (mAb) binding to the receptors of circulating blood cells, and immunohistochemistry (IHC) is usually used to assess the selective localization of target proteins in tissue specimens. 8,11 Studies have shown that molecular imaging can be used to assess target engagement.…”
Section: Introductionmentioning
confidence: 99%
“…8,15 Second, it can provide real-time and accurate systemic antibody IHC imaging of the whole body simultaneously, not only for all tumor lesions and their metastases but also for normal tissues, such as the spleen, which is an immune organ that is expected to predict the safety of antibody immunotherapy. 17 In addition to its use in PK investigations of mAbs, 18 including BsAbs 19,20 and antibody-drug conjugates (ADCs), 21 recent studies 1,4,13 have shown that the target engagement for mAbs can be assessed by PET. The assessment of BsAbs, however, is more urgent and difficult than that for canonical (i.e., monospecific) mAbs.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Journal of Nuclear Medicine, Menke-van der Houven van Oordt et al report an immuno-PET study with 89 Zr-labeled GSK2849330 antihuman epidermal growth factor receptor-3 (HER3) mAbs in 6 patients with HER3-positive tumors (8). Tumor and normal-tissue uptake were evaluated, and the effect of therapeutic doses of GSK2849330 mAbs (GlaxoSmithKline) on tumor uptake was assessed as an indicator of receptor occupancy.…”
mentioning
confidence: 99%
“…In the current clinical study (8), it was determined that an 8-mg mass dose (37 MBq) was sufficient to avoid rapid elimination of 89 Zr-GSK2849330 from the blood. This dose provided liver uptake equivalent to a larger mass dose (24 mg) and permitted tumor visualization (8). PET scans were acquired at 48 and 120 h after injection of 89 Zr-GSK2849330.…”
mentioning
confidence: 99%
See 1 more Smart Citation